Development of Smart Board Media Subject Material Predicate Object Description Subject Indonesian Language Class II A SDN Sukabumi II City Probolinggo - Yuni Wulandari; Ribut Prastiwi Sriwijayanti; Shofia Hattarina; Didit Yulian Kasdriyanto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Class II A teachers rarely utilize learning media in the classroom, relying primarily on textbooks. As a result, students often feel bored and disengaged, making the learning process less interactive and ineffective. This research aims to develop a smart board learning media, assess its validity, and evaluate its effectiveness in teaching subject matter, predicates, objects, and information. This study follows a research and development (R&D) approach using the ADDIE model, which consists of five stages: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The research was conducted in Class II A at SDN Sukabumi 2, Probolinggo City. Data collection was carried out through questionnaires distributed to material/content expert validators, media experts, teachers, and students. The results of the product trial indicate that the smart board media received a validity score of 94% from material/content experts and 91% from media experts. These scores fall within the 90–100% range, categorizing the media as highly valid. Field trials further demonstrated its effectiveness, with Class II A teachers rating it at 93% (very effective) and students at 87% (effective). In conclusion, the smart board media serves as an effective teaching aid, enhancing the learning experience for Class II A students at SDN Sukabumi 2. Future research could expand the development of smart board media for broader subject areas, ensuring greater engagement and motivation in the classroom.